â€œCRIMINAL POLICYâ€ DI MASA PANDEMI COVID-19 - Edi Saputra Hasibuan (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
A large country is born from an intelligent government, especially in solving problems and obstacles that always come their way. Likewise today, the emergence of the Covid-19 virus has become a real attack that is not only felt by one or two regions, but throughout the world. This often makes leaders move quickly and swiftly in taking action. Indonesia, which has also felt the massive impact of this pandemic, has made various efforts, both handling and prevention. The National Police, which is at the forefront of security issues in the country, was immediately deployed to curb and secure every area that became a red zone for the spread of the Covid-19 virus. The implementation of the PSBB and health protocols in each region is implemented by involving the National Police. This turned out to encourage the National Police to make new and effective breakthroughs or policies in order to maintain the situation and order during this pandemic.